1999
DOI: 10.1021/bi990563r
|View full text |Cite
|
Sign up to set email alerts
|

The Aβ 3-Pyroglutamyl and 11-Pyroglutamyl Peptides Found in Senile Plaque Have Greater β-Sheet Forming and Aggregation Propensities in Vitro than Full-Length Aβ

Abstract: A beta isolated from neuritic plaque and vascular walls of the brains of patients with Alzheimer's disease has been shown to contain significant quantities of A beta peptides which begin at residue 3Glu or 11Glu in the form of pyroglutamyl residues (A beta 3pE and A beta 11pE). To investigate the effects of these N-terminal modifications on the biophysical properties of A beta, peptides A beta 1-40, A beta 3pE-40, A beta 11pE-40, A beta 1-28, A beta 3pE-28, and A beta 11pE-28 were synthesized. Using circular d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
226
2
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 210 publications
(238 citation statements)
references
References 30 publications
9
226
2
1
Order By: Relevance
“…Additionally, A␤ pE3 is known to have a high aggregation propensity (54,55), increased stability (56), enhanced toxicity compared with fulllength A␤ (57), and dramatically reduced solubility at physiological pH-conditions (58). Our findings go along with the A␤ pE3 seeding hypothesis (20,54,57). Here, we further corroborate the importance of A␤ pE3-42 in the etiology of AD by demonstrating the effects of elevating A␤ pE3-42 in 5XFAD mice.…”
Section: Discussionsupporting
confidence: 81%
“…Additionally, A␤ pE3 is known to have a high aggregation propensity (54,55), increased stability (56), enhanced toxicity compared with fulllength A␤ (57), and dramatically reduced solubility at physiological pH-conditions (58). Our findings go along with the A␤ pE3 seeding hypothesis (20,54,57). Here, we further corroborate the importance of A␤ pE3-42 in the etiology of AD by demonstrating the effects of elevating A␤ pE3-42 in 5XFAD mice.…”
Section: Discussionsupporting
confidence: 81%
“…In addition, the formation of the N-terminal pyroglutamate, which is resistant to degradation by peptidases, increases the stability of the peptide. He and Barrow (46) reported that A␤ pE3-x peptides show enhanced ␤-sheet formation and aggregation propensity in aqueous and hydrophobic media compared with full-length A␤. They suggested that the loss of three charged groups facilitates and stabilizes ␤-sheet formation by reducing the level of unfavorable charge repulsion between strands (46).…”
Section: Biochemical Properties Of Pyroglutamate A␤mentioning
confidence: 99%
“…A␤ peptides were synthesized using manual solid-phase Boc (N-tert-butoxycarbonyl) amino acid chemistry as previously described (He and Barrow, 1999). Peptides were cleaved from the resin using anhydrous hydrogen fluoride with p-cresol/pthiocresol as scavengers.…”
Section: Synthesis Of A␤ Peptidesmentioning
confidence: 99%